A RARE UNDIAGNOSED CASE OF OSGOOD SCHLATTER DISEASE AND ITS REHABILITATION. - Muskan Prakash Bhojwani; Tabish Fahim; Geetika Gaikwad; Hiral lodhiya; Payal Jadhav; Shital khupse; Syeda Tazmin Fatima (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Osgood-Schlatter disease is a self-limiting, mostly benign knee disorder that most commonly affects fast-growing, athletically active adolescents. In active teens, it is a common source of pain and tenderness in the tibial tuberosity. It’s usually a self-limiting syndrome that comes and goes, although it can take months or years to fully resolve. Clinical and radiological examinations are used to make a diagnosis. Analgesics and limits on physical activities involving the knee are common management options. Physical therapy evaluation is outlined, followed by approaches for pain control and stretching exercises for the quadriceps and hamstrings, with a focus on muscular stiffness as a probable causal component. Ice massage is recommended for treating post-exercise soreness in the tubercle area. Certain therapy techniques, such as quadriceps stretching and strengthening, appear to be useful, for patients with OSD.